Kondisi Psikologis Masyarakat pada Puisi “Al-Kūlīra” Karya Nāzik Al-Malāikah dan “Lockdown” Karya Simon Armitage - Maulana, Gilang Inggit; Tasnimah, Tatik Mariyatut; Wahyudi, Jarot (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
The psychological condition of each country experiencing an epidemic in every era is certainly different. This paper describes the psychological condition in the poem